ROLE OF NON COAXIAL BONE MARROW BIOPSY NEEDLE AND BONE BIOPSY NEEDLE IN CT GUIDED CORE NEEDLE BIOPSIES - Saleem, Hassan; Rana, Atif Iqbal; Kiani, Ehsan Masud; Ramzan, Muhammad Mubashir; Naseem, Sajida; Chahuadhary, Muhammad Yousuf (Journal of Postgraduate Medical Institute, 2016)
Objective: To compare bone marrow biopsy needle (BMBN) with bone biopsy needle (BBN) in CT guided core biopsies considering size of core, diagnostic yield and cost of needles. Methodology: Retrospective study was done on 50 out of 68 patients re -ferred to Interventional Radiology department for CT guided bone biopsy from 2008 till 2013. Grading of specimen length was done as small, medium and large. Diagnostic yield was determined on basis of clinical, imaging and histopathology data. Local cost of both needle types was determined. Comparison was made and statistical analysis was performed. Results: Biopsy was performed by BBN in 16 patients and by BMBN in 34 patients. Overall diagnostic yield of bone biopsies was 82 % (41 of 50 biop-sies). Diagnostic yield with BMBN was 85 % and with BBN was 75 %. Overall longer specimen length was obtained using BMBN. Statistically, there was no significant difference between them in diagnostic yield and specimen length; however, BMBN costs almost one half than BBN. Conclusion: Diagnostic yield and sample length using bone marrow biopsy needle proved to be equivalent to bone biopsy needle. Bone marrow biopsy needle has an added benefit of being low in cost. Despite being a non-coaxial technique these needles can achieve diagnostic yield comparable to that of coaxial techniques as reported in past literature.